2014
DOI: 10.1192/bjp.bp.112.122663
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of remission with interpersonal counselling or drug treatment in primary care patients with depression: randomised controlled trial

Abstract: We identified some patient characteristics predicting a differential outcome with pharmacological and psychological interventions. Should our results be confirmed in future studies, these characteristics will help clinicians to define criteria for first-line treatment of depression targeted to patients' characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…The results of this preliminary study show that both IPC and IPT are helpful for previously untreated primary care patients with mild to moderate major depression. The remission rate for the IPC group in BDI, 61%, was approximately the same as in the earlier, shorter follow-up study of Menchetti et al (2014), in which the proportion of depressed primary care patients who achieved remission on the Hamilton Rating Scale for Depression (HRSD, 21-item) after two months of IPC was 59%. Comparison of the results with those of practice-based studies in routine service settings is more complicated, because the recovery rates depend upon how the sample is chosen (Barkham et al, 2012).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The results of this preliminary study show that both IPC and IPT are helpful for previously untreated primary care patients with mild to moderate major depression. The remission rate for the IPC group in BDI, 61%, was approximately the same as in the earlier, shorter follow-up study of Menchetti et al (2014), in which the proportion of depressed primary care patients who achieved remission on the Hamilton Rating Scale for Depression (HRSD, 21-item) after two months of IPC was 59%. Comparison of the results with those of practice-based studies in routine service settings is more complicated, because the recovery rates depend upon how the sample is chosen (Barkham et al, 2012).…”
Section: Discussionsupporting
confidence: 70%
“…Menchetti et al (2014) recently evaluated the efficacy of IPC as compared with selective serotonin reuptake inhibitors (SSRIs) in 287 depressed primary care patients in Italy. The proportion of patients who achieved remission at 2 months following IPC was 58.7%, significantly higher than with SSRIs (45.1%).…”
Section: Is Interpersonal Counselling (Ipc) Sufficient Treatment For mentioning
confidence: 99%
See 1 more Smart Citation
“…Menchetti et al (2013) reported that the proportion of patients with mild depression who achieved remission (Hamilton score of 7 or less) at 2 months was significantly higher in the IPC than the SSRI group. Interpersonal Counseling and SSRI appeared equally effective in treating moderate to severe depression.…”
Section: Testing Ipcmentioning
confidence: 99%
“…Menchetti et al (2010, 2013) conducted a multi-center randomized controlled trial in primary care centers in Italy, comparing the effectiveness of IPC to selective serotonin reuptake inhibitors (SSRIs). Patients with depressive symptoms were referred by primary care physicians.…”
Section: Testing Ipcmentioning
confidence: 99%